2022
DOI: 10.1002/pen.26193
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, properties, and applications of polylactic acid‐based polymers

Abstract: Polylactic acid (PLA) is known as one of the greatest promising bioabsorbable and compostable polyesters with the capability of high molecular weight synthesis. Lactic acid condensation, azeotropic dehydration, and condensation ring‐open polymerize of lactide are three methods for PLA polymerization. Comprehension of material properties is critical for choosing the right processing method and adjusting PLA characteristics. A variety of mechanical properties of this material, from soft and elastic to stiff and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 210 publications
1
51
0
Order By: Relevance
“…These results indicated that the varied combinations of parameters would affect the tensile performances of finished specimens. In addition, low standard deviations of maximum tensile strength and Young's Modulus can be found in Table 4, which agrees with the tensile behaviors of half thickness series samples in previous publications both for ABS samples and PLA specimens 40,41 . This indicates a superior flexibility in these samples, 46 making overmolding technique popularized in manufacturing industry, such as aerospace products and electronic components.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…These results indicated that the varied combinations of parameters would affect the tensile performances of finished specimens. In addition, low standard deviations of maximum tensile strength and Young's Modulus can be found in Table 4, which agrees with the tensile behaviors of half thickness series samples in previous publications both for ABS samples and PLA specimens 40,41 . This indicates a superior flexibility in these samples, 46 making overmolding technique popularized in manufacturing industry, such as aerospace products and electronic components.…”
Section: Resultssupporting
confidence: 88%
“…Regarding the manufacturing time for the FDM and IM specimens, Gong et al shows it takes 6 min to fabricate one PLA specimen using FDM only. In converse, two IM specimens can be fabricated in 90 s 41 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations